Assessing Conformity of Scientific Voices and Local Needs to Combat Forest Fire in Indonesia - Meti Ekayani; Dodik Ridho Nurrochmat; Bambang Hero Saharjo; James Thomas Erbaugh (Institut Pertanian Bogor (IPB University), 2015)
This study evaluates the compatibility of scientific voices with the needs to combat forest fire as perceived by relevant stakeholders through a review of scholarly output, an evaluation of the conformity between scientists and stakeholder views on forest fire issues, and an analysis of how different types of scientists and voice channels contribute the local needs to combat forest fire in Indonesia. This research indicates that although forest fire has cross-country border impacts, forest fire discourses were dominated by home country issues rather than the concerns of global forest fire events. Further, although information about forest fire is widely available in the scientific journals, the “knowledge utilization” of this information remains low. To improve “knowledge utilization”, scientists can use different channels to disseminate information, in addition to scientific journals. While social-economic aspects are perceived to be the prime problem of forest fire in Indonesia, the minimal presentation of social scientists within forest fire discourse is a concern. To address these primary concerns within and outside scientific journals, the involvement of social scientists within the forest fire discourse is very important.